PERFORMANCE REVIEW: KEEPING IT FEASIBLE - Adiningrum, Tatum Syarifah (Journal of Business Strategy and Execution, 2011)
The strategic human resource management (SHRM) approach tries to link all aspects and practices in HRM directly to organizations’ goals. One of the most important aspects in SHRM is the performance management, in which the HR manager make sure that employee performance are on target, by applying practices such as performance review and merit rating. The following paper discussed the performance review process, what factors make an effective performance review and the benefits of the process, highlighting important aspects of a successful strategic model of performance management, using the strategic model of management of performance. Effective performance review depends to commitment of the organization. Entailed in the commitment is the willingness of the organization to develop a suitable method of train the appraiser to make sure that they fully understand and that they believe in the process. Another important factor is that performance review process should be aligned with organization goals to give it the right direction and fair standard.